Daur Ulang Limbah Plastik Polyethylene Terephthalate (PET) dan Abu Terbang (Fly Ash) Menjadi Paving Block - Lestari Riyandini, Vina; Sawir, Hendri; Ilham, Syukri (Journal of Applied Civil Engineering and Infrastructure Technology, 2024)
Plastic waste that was disposed of carelessly into the environment causes side effects, namely for groundwater, and was difficult for the soil to decompose, even for hundreds of years. Meanwhile, fly ash has the potential to pollute rivers and seas which were the center of life for coastal communities. Therefore efforts were made to utilize this waste, one of which was in the manufacture of paving blocks. Paving block was a means of transportation that was commonly used in road pavements. This study aims to utilize PET and fly ash plastic waste and determine whether the resulting paving blocks meet standards. This study used a simple method, namely heating PET plastic using a paint-fired gas stove mixing fly ash, and then molding it with the composition of each material, namely 0,5 kg (plastic): 1,5 kg (fly ash), 1 kg (plastic): 1 kg (fly ash), and 1,5 kg (plastic): 0,5 kg (fly ash). The resulting paving blocks were tested for quality according to SNI 03-0691-1996 standards. Based on the research results, the best paving block was obtained with a mixture composition of 1 kg (plastic): 1 kg (fly ash) which has a compressive strength value that almost meets the standard, which was 8.30 MPa and a water absorption capacity of 15.20 %.